1992
DOI: 10.1002/j.1460-2075.1992.tb05045.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of B-DNA containing O6-ethyl-G-C base pairs stabilized by minor groove binding drugs: molecular structure of d(CGC[e6G]AATTCGCG complexed with Hoechst 33258 or Hoechst 33342.

Abstract: O6‐ethyl‐G (e6G) is an important DNA lesion, caused by the exposure of cells to alkylating agents such as N‐ethyl‐N‐nitrosourea. A strong correlation exists between persistence of e6G lesion and subsequent carcinogenic conversion. We have determined the three‐dimensional structure of a DNA molecule incorporating the e6G lesion by X‐ray crystallography. The DNA dodecamer d(CGC[e6G]AATTCGCG), complexed to minor groove binding drugs Hoechst 33258 or Hoechst 33342, has been crystallized in the space group P212121,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
70
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 29 publications
5
70
0
Order By: Relevance
“…On the other hand, no global conformation change due to 8-oxo-G was observed in NMR and circular dichroism studies (51,52). There was no bending in the crystal structures of dodecamer duplexes containing an O 6 -ethylguanine⅐cytosine pair, although they were complexed with minor groove binding drugs (53,54), and even when O 6 -Me-G was opposite adenine, the overall structure of this mispaired dodecamer duplex was very close to that of the parent duplex (55). NMR studies of duplexes containing a T⅐T mismatch (56) and a nick (57) revealed that these lesions had little influence on the conformation of the normal B-form DNA.…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, no global conformation change due to 8-oxo-G was observed in NMR and circular dichroism studies (51,52). There was no bending in the crystal structures of dodecamer duplexes containing an O 6 -ethylguanine⅐cytosine pair, although they were complexed with minor groove binding drugs (53,54), and even when O 6 -Me-G was opposite adenine, the overall structure of this mispaired dodecamer duplex was very close to that of the parent duplex (55). NMR studies of duplexes containing a T⅐T mismatch (56) and a nick (57) revealed that these lesions had little influence on the conformation of the normal B-form DNA.…”
Section: Discussionmentioning
confidence: 93%
“…The change in surface area on binding, ÁA, is the difference between the area of the complex and the summed surface areas for the drug-free native duplex and the ligand molecule separated from each complex. High-resolution crystal coordinates are not available for the free dye, but comparison with the ligands separated from other DNA-Hoechst 33258 crystal structures (Pjura et al, 1987;Teng et al, 1988;Quintana et al, 1991;Sriram et al, 1992) showed only $2 to 3% variation in surface areas for the bound molecules. Similarly, calculated areas for a minimized model ligand constructed using standard bond and angle geometries differed by <2% from the experimental DNA-bound values.…”
Section: Calculation Of Solvent-accessible Surface Areasmentioning
confidence: 96%
“…Both high-®eld solution NMR and X-ray crystallographic methods have been used to examine the complexes formed between Hoechst 33258 and a variety of oligonucleotides (Pjura et al, 1987;Teng et al, 1988;Parkinson et al, 1990;Searle & Embrey, 1990;Fede et al, 1991;Quintana et al, 1991;Sriram et al, 1992). Thus, structural studies with the 12-mer d(CGCGAATTCGCG) 2 duplex reveal a 1:1 binding stoichiometry with the bound ligand positioned in the minor groove AT-tract.…”
Section: Introductionmentioning
confidence: 98%
“…It is an N-methyl piperazine derivative with two benzimidazole groups and one phenol group. Many structural variants of Hoechst 33258 have been synthesized in order to modify the AT selectivity using chemical changes in benzimidazole systems (Sriram et al, 1992;Bailly et al, 1994). Chemical modifications in the phenol group have also been performed to add additional sequence-determining features to the ends of the molecule (Ebrahimi et al, 1992;Parkinson et al, 1994).…”
mentioning
confidence: 99%